Clinical course and pancreas parenchyma sparing surgical treatment of severe pancreatic trauma. Issue 9 (September 2020) - Chikhladze, S.; Ruess, D.A.; Schoenberger, J.; Fichtner-Feigl, S.; Pratschke, J.; Hopt, U.T.; Bahra, M.; Wittel, U.A.; Globke, B.
Highlights: Severe pancreatic trauma represents a major challenge for interdisciplinary trauma teams and management remains highly individualized. Determination of main pancreatic duct involvement is crucial for appropriate clinical decision-making; to this end, if possible, MRI or ERP should be performed next to standard trauma CT scans. For grade III/IV pancreatic trauma with distal/proximal transection of the gland, parenchyma-preserving procedures appear safe and should be considered. Abstract: Introduction: Pancreatic trauma (PT) involving the main pancreatic duct is rare, but represents a challenging clinical problem with relevant morbidity and mortality. It is generally classified according to the American Association for the Surgery of Trauma (AAST) and often presents as concomitant injury in blunt or penetrating abdominal trauma. Diagnosis may be delayed because of a lack of clinical or radiological manifestation. Treatment options for main pancreatic duct injuries comprise highly complex surgical procedures. Patients and Methods: We retrospectively analyzed clinical data from 12 patients who underwent surgery in two tertiary centers in Germany during 2003–2016 for grade III-V PT with affection of the main pancreatic duct, according to the AAST classification. Results: The median age was 23 (range: 7-44) years. In nine patients blunt abdominal trauma was the reason for PT, whereas penetrating trauma only occurred in three patients. MRI outperformed classical trauma CT imaging with regard to detection of duct involvement. Complex procedures as i.e. an emergency pancreatic head resection, distal pancreatectomy or parenchyma sparing pancreatogastrostomy were performed. Compared to elective pancreatic surgery the complication rate in the emergency setting was higher. Yet, parenchyma-sparing procedures demonstrated safety. Conclusions: Often extension of diagnostics including MRI and/or ERP at an early stage is necessary to guide clinical decision-making. If, due to main duct injuries, surgical therapy for PT is required, we suggest consideration of an organ preservative pancreatogastrostomy in grade III/IV trauma of the pancreatic body or tail.